Enhanced electro-Fenton degradation of tetracycline in aqueous solution using a self-supported BiOCl/CF cathode. (27th July 2022) - Kuai, Jiangshan; Geng, Xiusen; Ren, Xiaohua; Guo, Weilin
Abstract: The cathode material is critical to the yield of hydrogen peroxide (H2 O2 ) and electro-Fenton (EF) performance. In this work, bismuth oxychloride (BiOCl) as one of the representatives of ternary oxides was grown in situ on carbon felt (CF) through a simple solvothermal method and employed directly as a self-standing cathode for the EF degradation of the target contaminant tetracycline (TC). TC can be almost completely degraded, up to 95% in 90 min under the heterogeneous EF process. The characterizations demonstrated that the BiOCl/CF electrode exhibited excellent conductivity due to CF as the supporting carbon material with a 3D network structure; meanwhile, this hybrid electrode also possessed abundant active sites attributed to the decorated BiOCl having rich oxygen defects. Finally, the rational reaction mechanism of TC was also elucidated by the X-ray photoelectron spectroscopy (XPS) spectrum, free radical quenching experiments and electron paramagnetic resonance (EPR) spectra, in which hydroxyl radicals ( ) were considered as the dominant active oxidants and BiOCl had a synergistic effect on in-situ generation and decomposition of H2 O2 . HIGHLIGHTS A BiOCl/CF composite electrode was prepared via a simple solvothermal method. Oxygen defects enriched BiOCl and bare carbon felt cathode had a synergistic effect on H2 O2 production. Lattice oxygen reduced Bi 3+ to Bi 0, facilitating the formation of by in situ reaction of hydrogen peroxide with Bi 0 . was the main radical in catalytic degradation of tetracycline. Graphical Abstract